How much is enough in watering plants? State-of-the-art in irrigation control: Advances, challenges, and opportunities with respect to precision irrigation - Owino, Lina; Söffker, Dirk (Frontiers in Control Engineering, 2022)
With a rapidly expanding global population placing an ever growing demand on freshwater resources, an increased focus on irrigation techniques tailored to the specific needs of plant appears as one solution to minimize overall freshwater consumption. Precision irrigation methods seek to realize an acceptable compromise between yield and irrigation water consumption. The main control variables of interest are the timing and quantity of water supplied to the crop, with the goal of maintaining the water content of the soil, achieving specific water use efficiency with regard to yield or maintaining the physiological response of the plant to water stress within predetermined limits. To adequately address irrigation water demand, the plant water status must be established and the difference between current state and the desired state at full irrigation supplied in a timely fashion. This is often achieved through soil measurements, which is however prone to error arising from heterogenous distribution of water in the soil. Growing research interest is observed detailing the determination of plant water status directly from physiological responses. This paper reviews irrigation control approaches based on different plant water status assessment techniques. A distinct focus is made on application scale of the discussed control approaches, an aspect that has not been considered intensively enough in previous discussions of irrigation control approaches. A discussion of the observed strengths and shortcomings and technological advances supporting the various methods used to quantify plant water status extends the review. Emerging trends that are likely to have an impact on plant water status determination and optimal timing and quantification of irrigation water requirements are integrated to show latest results.